# How would you translate $\neg(P\to \neg Q )$ into English?

I am having trouble in how to translate the $\neg(P\to \neg Q )$ into English. I attempted first letting P and Q represent certain statements. For instance, let $P$ be the statement "I will gather the ingredients," and let $Q$ represent "I will cook a meal." Then the statement would represent:

"It is not the case that gathering ingredients is a sufficient condition for me to not cook a meal."(Correct me if I translated it wrong; this is why I'm asking this question)

One side note is that when you simplify the statement $\neg(P\to \neg Q )$ it is equivalent to the statement $P \land Q$. Furthermore, when I translate using my example, it means "I will get ingredients, and I will cook a meal."However, that sounds like cheating since it does not feel like it represents the statement $\neg(P\to \neg Q )$ . Anyhow, would that still be an acceptable besides my answer,"It is not the case that gathering ingredients is a sufficient condition for me to not cook a meal." Also, is my former answer a good representation for the statement $\neg(P\to \neg Q )$? Do you know any alternative answers for the translation of $\neg(P\to \neg Q )$?

• I think translation should get at the logical content, and $P\land Q$ is a lot easier to translate to idiomatic English. Trying for "word for word" translation risks introducing ambiguities. Your proposed sentence, though technically correct, is not easy to decipher. – André Nicolas Sep 23 '13 at 16:27
• It is never the case that suffiency of ingredients has ever led to a meal not being given – ARi Sep 23 '13 at 16:27
• Let $P$: “I will cook." and $Q$: “I will not gather." Reformulate. – Michael Hoppe Sep 23 '13 at 16:31
• It has never been that ingredients were sufficient and a meal was not cooked – ARi Sep 23 '13 at 17:10
• It is not the case that "if p, then not q". – Doug Spoonwood Sep 24 '13 at 0:04

Yes, you're correct in your translations: both the direct translation, and the translation of the equivalent statement.

Your translation of the equivalent statement $P \land Q$ certainly sounds more direct, and it expresses, logically, exactly what your first translation conveys.

As an alternative to your first translation, you might instead want to say, directly from the given expression $\lnot (P \rightarrow \lnot Q)$, using the $P$ and $Q$ you designated:

"It is not the case that, if I gather the ingredients, then I won't cook the meal."

Maybe that sounds nicer to you than the sufficiency statement. But to get to the point:

I think that your observation that the given proposition simplifies to the equivalent proposition: $$\lnot (P \rightarrow \lnot Q) \equiv P \land Q$$ gives you license to use the most direct of your translations:

"I will gather the ingredients, and I will cook the meal."

• K≡NCN and C≡NKN. C≡AN, and A≡CN. Alright, that isn't clear and I've mixed things all up there. I mean, 1. pqK≡pqNCN and 2. pqC≡pqNKN, as well as 3. Cpq≡ANpq and 4. A≡CNpq. Thus, if you write formulas in prefix notation you can replace any instance of "C" with "AN", and "A" with "CN". If you write in postfix notation you can replace any instance of "K" with "NCN" and any instance of "C" with "NKN". – Doug Spoonwood Sep 24 '13 at 0:11
• @Doug, please do not leave comments that are meaningless to most newcomers to logic, and unwelcome by most others: If you want to be helpful, translate to a more familiar "language" than the one you're obsessively and compulsively attached to. – amWhy Sep 27 '13 at 15:26
• I doubt very much that Polish notation or reverse Polish notation comes as unwelcome by "most others", and even if so it has never gotten rejected by logicians in general. It is not possible to express what {K≡NCN, C≡NKN}, and {C≡AN, A≡CN} allow you to do in familiar infix notation, because for formulas in infix notation you have to find where everything lies to perform similar manipulations. You don't have to do this in prefix or postfix notation. And I've mentioned two languages here, so your comment simply lacks coherence. – Doug Spoonwood Sep 27 '13 at 23:55

Let $P$ be the statement "It is raining today". Let $Q$ be the statement "I will go outside today". For a lot of people, $P \rightarrow \neg Q$ - "if it is raining, I will not go outside today".

I'm generally alright with rain, though, so this statement doesn't apply to me - its negation applies to me. $\neg (P \rightarrow \neg Q)$ - "it is not that case that, if it is raining, I will not go outside", alternatively "rain does not prevent me from going outside".

You wouldn't believe that this were true unless you had actually seen me go out in the rain, in the same way that the statement $\neg (P \rightarrow \neg Q)$ is equivalent to $P \wedge Q$ - "it is raining, and I am outside". If you knew that I was out in the rain, then you'd know that rain doesn't prevent me from going outside. To give credence to the idea that rain doesn't prevent me from going outside, I must have been out in the rain before, so yes, your former answer is a good representation for the statement $\neg (P \rightarrow \neg Q)$. "$P$ does not prevent $Q$" is another way to phrase it.

What is being missed here is the " implies relation" I would say
Not the case such that P implies not happening of Q ...ie

Incorrect to say that P prevents Q

Never has my not $\underbrace {cooking \quad meal}_Q$ been decided by my ability to $\underbrace {gather \quad ingredients} _P$.

Never could my success in gathering ingredients prevent me from cooking a meal.

## Never does a Downpour prevent me from going outside.

So what we gather is: " A implies not B" can be translated as 'A prevents B'

Given $P$, $Q$ is possible.

Or, $P$ doesn't rule out $Q$.